Proximity of signallers can maintain sexual signal variation under stabilizing selection. Issue 1 (December 2017) - van Wijk, Michiel; Heath, Jeremy; Lievers, Rik; Schal, Coby; Groot, Astrid
Abstract How sexual communication systems can evolve under stabilizing selection is still a paradox in evolutionary biology. In moths, females emit a species-specific sex pheromone, consisting of a blend of biochemically related components, to which males are attracted. Although males appear to exert strong stabilizing selection on female pheromone, these blends seem to have evolved rapidly, as evidenced by ~120, 000 moth species. Here we propose and test a "proximity model" wherein two females that vary in their relative attractiveness to males, can both benefit from calling in close proximity to each other. In a field study, we show that (1) artificially selected unattractive females can achieve mating rates comparable to attractive females if they signal in close proximity to attractive females, and (2) attractive females benefit from higher mating rates when signalling in close proximity to unattractive females. We propose that frequency-dependent behavioural and spatial interactions can sustain signal variation within populations even when these signals are under stabilizing selection.